The Role and Competencies of Merdeka Teachers in the Midst of Digital Era Disruption: Basis for Developing Competencies of Generation Alpha Students - Vioreza, Niken; Utami, Purwani Puji; Nugraheny, Devita Cahyani (S&Co Publishing, 2025)
This research aims to identify the characteristics of students in the digital era and explain the roles and competencies needed by Merdeka teachers in facing digital era disruption. The research method used in this research is a literature review using techniques of observing, reading, collecting, and analyzing data from various sources such as books, journals, reports, relevant documents. The results of this research reveal that the role of Merdeka teachers is as a learning facilitator who supports the competence of generation alpha students to think critically, communicate, collaborate, and have strong character. In order to develop the competencies of generation alpha students, teachers need to understand their role and the various competencies they must have today. Teachers need to have a broad horizon of knowledge, have a global perspective, the ability to analyze a problem, data-based research skills, and most importantly be willing to open their mental block to technology. The implications of this research can be used as a basis for curriculum development and teacher training that is more appropriate to the needs of students in this digital era.